Tonal reflexes of movement in Asante Twi - Korsah, Sampson; Murphy, Andrew (Natural language and linguistic theory, 2020)
We argue that Asante Twi has a process of tonal overwriting on verbs that are crossed by an A’-dependency. It is shown that this view captures the distribution of the process across ex-situ focus constructions, relative clauses and adverbial clauses, which are all contexts involving operator movement. Furthermore, we illustrate that this process is unbounded and applies to each verb in a long-distance dependency. We therefore conclude that this is a reflex of successive-cyclic movement through v P. Additionally, we provide a detailed study of resumption in Asante Twi, showing that despite island-insensitivity, resumption is still derived by movement. Finally, the morpho-phonological side of the phenomenon is investigated. It is shown that overwriting affects only those affixes below v and not those above, which follows from cyclic Vocabulary Insertion. This provides support for Kandybowicz’ ( 2017 ) assumption that aspect and negation are lower than v P in Asante Twi.